Impacts of an Exercise Program and Motivational Telephone Counseling on Health-Related Quality of Life in People With Parkinson's Disease. Issue 3 (May 2019) - Lee, JuHee; Choi, MoonKi; Yoo, Yonju; Ahn, Sangwoo; Jeon, Justin Y.; Kim, Ji Young; Byun, Ji Yong
Abstract: Purpose: The purpose of this study was to test the effects of group exercise and telephone counseling on physical and psychosocial health in people with Parkinson's disease (PD). Design: This was a quasiexperimental study with a nonequivalent control group. Methods: This study took place in Seoul, South Korea. Twenty-two and 20 subjects participated in the intervention and comparison groups, respectively. The intervention group performed group exercises twice a week and received motivational telephone counseling every 2 weeks for 12 weeks. Findings: Significant effects of the intervention were found in overall health-related quality of life (HRQOL; p = .012) and in the following HRQOL dimensions: stigma ( p = .026), social function ( p = .003), cognition ( p = .028), and communication ( p = .014). No other variables such as activities of daily living, functional fitness, and depression exhibited statistically significant effects. Conclusion/Clinical Relevance: These results indicate that group exercise with telephone counseling positively affects some aspects of HRQOL in PD patients.